Job Seekers' Awareness towards the Public Employment Services of the Local Government Unit of Tangub City - Gupit, John Jem; Bajao, Analyn; Torrion, Voltaire B. (Future Science / FSH-PH Publications, 2025)
This study aimed to assess the level of awareness among recent graduates of Northern Mindanao State College (NMSC) and Tangub City Global College (TCGC) towards the services offered by the Public Employment Service Office (PESO) of Tangub City. Specifically, the study investigates awareness of referral and placement, labor market information, employment coaching, and job fair programs. A quantitative research design was employed, utilizing a modified questionnaire administered to 466 recent graduates selected through purposive sampling. Data were analyzed using descriptive statistics, particularly weighted mean. The findings revealed that while the respondents were aware of PESO's referral and placement, employment coaching and career counseling, and job fair services, their awareness of labor market information was relatively low. These insights highlight the need for PESO to enhance its information dissemination strategies to improve understanding, particularly regarding labor market trends and opportunities.